THE USE OF PERSONAL DEIXIS IN THE STORY “THE NOSE” BY NIKOLAI VASILIEVICH GOGOL - Alikulova Shaxnoza Abdimuminovna (“SUN’IY INTELLEKTNING TIL O‘RGANISHDAGI O‘RNI” MAVZUSIDA TALABALAR ILMIY-AMALIY KONFERENSIYASI, 2025)
This study explored the application of deixis in Nikolai Vasilievich Gogol’s novel The Nose. Deixis is a part of pragmatics that discusses the context in an utterance. The purpose of this study was to find out the types of deixis used in the story and to analyze the function of the deixis found in the story The Nose. In analyzing deixis, this study used Yule’s theory (1996) which divides deixis into three categories: person deixis, spatial deixis, and temporal deixis. Person deixis is used to show people, spatial deixis is used to show location, and temporal deixis is used to show time. This study belongs to qualitative research with descriptive qualitative because the data was obtained in the form of words or utterances. In collecting the data, this study used the documentation method which was carried out through note-taking and reading strategies. The results showed that there were three types of deixis found in the story The Nose. They were person deixis, spatial deixis, and temporal deixis. There were a total of 608 deixis data found. Among them were 502 person deixis, including 151 first person deixis, 92 second person deixis, and 259 third person deixis. Meanwhile, there were 75 spatial deixis data and 32 temporal deixis data.